The Impact of Rights Issues on Capital Structure and Profitability of Banking Companies Listed on the Indonesia Stock Exchange: A Comparative Analysis Before and After Rights Issues: A Comparative Analysis Before and After Rights Issues - Irma, Irma; Antong, Antong; Rismawati, Rismawati (PT. EQUATOR SINAR AKADEMIA, 2025)
This study investigates the impact of rights issues on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using a comparative analysis of key financial ratios—Current Ratio (CR), Debt-to-Equity Ratio (DER), Return on Assets (ROA), Net Profit Margin (NPM), and Price-to-Earnings Ratio (PER)—the research aims to determine whether significant differences exist before and after rights issues. The findings reveal that rights issues significantly improve liquidity (CR) and market valuation (PER) while reducing reliance on debt (DER). However, profitability ratios (ROA and NPM) decline, indicating inefficiencies in asset utilization and operational performance. The results align with the Signaling Theory and Pecking Order Theory, suggesting that rights issues send positive market signals but require better capital management to enhance profitability. This study contributes to the literature by providing sector-specific insights into the banking industry in an emerging market context, offering valuable implications for management and investors. Abstrak: Penelitian ini mengkaji dampak rights issue terhadap kinerja keuangan perusahaan perbankan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2019-2023. Dengan menggunakan analisis komparatif terhadap rasio keuangan utama—Current Ratio (CR), Debt-to-Equity Ratio (DER), Return on Assets (ROA), Net Profit Margin (NPM), dan Price-to-Earnings Ratio (PER)—penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan signifikan sebelum dan setelah rights issue. Hasil penelitian menunjukkan bahwa rights issue secara signifikan meningkatkan likuiditas (CR) dan valuasi pasar (PER) serta mengurangi ketergantungan pada utang (DER). Namun, rasio profitabilitas (ROA dan NPM) mengalami penurunan, mengindikasikan inefisiensi dalam pemanfaatan aset dan kinerja operasional. Temuan ini sejalan dengan Signaling Theory dan Pecking Order Theory, yang menyatakan bahwa rights issue memberikan sinyal positif kepada pasar namun memerlukan manajemen modal yang lebih efektif untuk meningkatkan profitabilitas. Penelitian ini memberikan kontribusi literatur dengan menyajikan wawasan spesifik sektor perbankan dalam konteks pasar berkembang, serta implikasi penting bagi manajemen perusahaan dan investor